Tax efficiency in selected Indian states - Raghbendra Jha, M. S. Mohanty, Somnath Chatterjee, Puneet Chitkara (Empirical Economics (1999) 24:641654, 1999)
This paper attempts to measure pure tax eciency of rfteen major Indian states (Andhra Pradesh, Assam, Bihar, Haryana, Gujarat, Karnataka, Kerala, Madhya Pradesh, Maharashtra, Orissa, Punjab, Rajasthan, Tamilnadu, Uttar Pradesh and West Bengal) for the period 198081 to 199293 in a manner that allows this eciency to vary both across time as well as across states. It is discovered that there is a moral hazard problem in the design of central grants in that higher grants by the central government to the state governments reduce eciency of tax collection by these states. The less poor states are more effcient in tax collection. The rankings of states by tax effciency for the various years do not converge. An index of aggregate tax effciency is calculated and it appears that this index has been stagnating. It is argued that the weight placed on tax e"ort in the formula determining central grants to state governments should be increased to improve tax effciency of state governments.